Chemical and Textural Re-equilibration in the UG2 Chromitite Layer of the Bushveld Complex, South Africa. (6th June 2018) - Veksler, Ilya V; Sedunova, Alena P; Darin, Andrey V; Anosova, Maria O; Reid, David L; Kaufmann, Felix E D; Hecht, Lutz; Trumbull, Robert B
Abstract: Variations of mineral chemistry and whole-rock compositions were studied in detail, at millimetre to centimetre intervals, in two vertical drill core profiles through the platiniferous UG2 chromitite layer in the western and eastern limbs of the Bushveld Complex, South Africa. Analytical methods included electron microprobe and LA-ICP-MS analyses of the main rock-forming minerals, orthopyroxene, plagioclase and interstitial clinopyroxene. One profile was also studied by synchrotron-source XRF. Statistical analysis of crystal size distribution of chromite was also performed at different levels in the chromitite layer and in adjacent silicate rocks. The results provide new evidence for chemical and textural late magmatic re-equilibration in the UG2 layer and in the silicate rocks at the contact zones. The chromite crystal size distributions imply extensive coarsening of that mineral within the main chromitite seam, which has erased any textural evidence of primary deposition features such as recharge or mechanical sorting of crystals, if those features originally existed. The mineral compositions in chromitite differ from those in adjacent silicate rocks, in general agreement with predictions of chemical re-equilibration with evolved, residual melt (the trapped liquid shift effect). In detail, the geochemical data imply, however, that the conventional trapped liquid shift model has shortcomings, due to the effects of material transport driven by chemical gradients between modally contrasting layers of crystal mush undergoing re-equilibration reactions. In the presence of such gradients, selective open-system conditions may hold for alkalis and hydrogen because of their higher diffusion rates in silicate melts. Differential mobility of components in the interstitial melt can also sharpen the original modal layering by causing minerals to crystallise in one layer and dissolve in another. Detailed trace element profiles by synchrotron XRF reveal an uneven vertical distribution of incompatible elements which implies that the permeability of the chromitite layer may have been significant, even at the latest stages of interstitial crystallization.